(untitled) - Lundbom, Jack R.; (1939-...) (U.S.A., 2015)
Through careful attention to the structure of Matthew's Gospel and the place of the Sermon within it, a keen sensitivity to the patterns and themes of Israelite prophecy, and judicious comparisons with other Jewish and rabbinic literature, Jack R. Lundbom elucidates the meaning of the Sermon and its continuity with Israel's prophetic heritage as well as the best of Jewish teaching. By deft appeal to Christian commentators on the Sermon, Lundbom brings its most important themes to life for the contemporary reader.
Keywords: Religion -- Biblical Studies -- Jesus, the Gospels & Acts